Rectangular Microstrip Patch Antenna Based on Resonant Circuit Approach - Zakaria, Zahriladha; Sam, Weng Yik; Abd Aziz, Mohamad Zoinol Abidin; Meor Said, Maizatul Alice (2012)
This paper presents the investigation based upon the resonant circuit approach to characterize the rectangular microstrip patch antenna from the low-pass prototype lumped element. The physical layout of the rectangular microstrip patch antenna based on single-mode and dual-mode will be established. An improvement on bandwidth of the antenna can be achieved by increasing the number of modes. In the paper, the understanding of microwave filter synthesis technique is applied in order to obtain the resonance at 2 GHz. A notch technique is used in the design to produce dual-mode frequencies on the microstrip patch antenna. The prototype circuit and proposed physical layout of the single and dual-mode microstrip patch antennas are demonstrated through the analysis of circuit and EM simulations in order to proof the proposed concept. This study would be useful to realize antenna for broadband applications as well as to investigate the appropriate technique for integrating antenna and microwave filter.